2018
DOI: 10.3329/jbcbm.v4i1.37879
|View full text |Cite
|
Sign up to set email alerts
|

Management of bacterial wilt (Ralstonia solanacearum) of potato: focus on natural bioactive compounds

Abstract: The bacterial wilt disease caused by Ralstonia solanacearum is an extremely destructive soil borne bacterial pathogen to potato. It appeared as rapid and fatal wilting symptoms in the host. The pathogen entered through different wounds and easily disseminated via infected biological material, soil, contaminated irrigation water, surface water, farm equipment etc. and could survive for many years in association with alternate hosts. It is a widely distributed and very much diversified soil borne pathogen having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 61 publications
0
26
0
Order By: Relevance
“…These bacteria are considered soil borne, so it's usually attack plants through the roots and colonizes xylem vessels ( García et al, 2019 ). As the vascular bundles in the diseased plants are filled with bacteria impede that transport of water and nutrients, and thus the symptoms appear, which are yellowing of the leaves, redness of the vascular bundles, necrosis, and ultimately the total wilt of the infected plants, then followed by physiological modifications in the diseased plants, such as increasing the respiratory rate and reducing transpiration and photosynthesis ( Karim and Hossain, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These bacteria are considered soil borne, so it's usually attack plants through the roots and colonizes xylem vessels ( García et al, 2019 ). As the vascular bundles in the diseased plants are filled with bacteria impede that transport of water and nutrients, and thus the symptoms appear, which are yellowing of the leaves, redness of the vascular bundles, necrosis, and ultimately the total wilt of the infected plants, then followed by physiological modifications in the diseased plants, such as increasing the respiratory rate and reducing transpiration and photosynthesis ( Karim and Hossain, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…As the disease incidence and severity varies between potato cultivars, due to the presence of genetic differences between ones. Studies have shown that Spunta and Bellini cultivars are among the most susceptible to the disease, unlike Mondial cultivar ( Karim and Hossain, 2018 ). So the studies illustrate that the highest genetic similarity was found between Bellini and Spunta as the closest but the lowest value was found between Mondial and Bellini as most distant ( ELHetawy, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Protection methods and chemical control of R. solanacearum are ineffective. Antibiotics show no effect and the biological control method has not yet been developed against this organism (Karim and Hossain, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to FAO and EU regulations, potatoes for exportation must be produced in pest-free areas (PFAs) mostly located in the newly reclaimed areas (NRAs). Meanwhile, controlling the disease in old potato fields is a complicated task, and single management regime showed limited success (Karim and Hossain 2018), in addition to the hazardous environmental impact. A study on the survival of the pathogen in Dutch versus Egyptian soil(s) was investigated and compared by Messiha NAS (2006) where survival of the pathogen and disease management was attributed to physical, chemical, and microbial factors.…”
Section: Introductionmentioning
confidence: 99%